2020 6th International Conference on Education and Technology (ICET) 2020
DOI: 10.1109/icet51153.2020.9276575
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Student Responses of Online Learning during the Covid-19 Pandemic in Performing Art Education

Abstract: The Covid-19 pandemic has had a massive impact on human life, including arts learning in higher education. The problems that arise cause the learning community in the classroom to be limited. Face-to-face teaching is suddenly replaced by online learning. This study aims to determine an Edmodo-based online class's feasibility by conducting a user response survey, namely students. The questionnaire was given to all active students majoring in Performing Arts Education from three batches, totaling 125. Data analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
10
0
2
Order By: Relevance
“…icra pratikleri (Cabedo-Mas, Arriaga-Sanz ve Moliner-Miravet, 2021; Chlu, 2020), çalgı eğitimcilerinin öğretme pratikleri (Bruin, 2021), yaşam doyumu, sosyal medya kullanımı ve müzik dinleme pratikleri (Krause vd., 2021), Amerika'da müziğin geleceği (Botstein, 2020), bütünsel iyilik, algılanan stres ve yenilikçi müzik terapi (Giardino vd.,, 2020; Gaddy vd., 2020), alkol, sigara ve ilaç bağımlılığı ve müzik terapi (Situmorang, 2020), İran müzik endüstrisi (Semati ve Behroozi, 2021), müzik ve pandemide kişilerarası ilişkiler (Philippe, Schiavio ve Biasutti, 2020), müzik tüketim araçları ve Spotify (Yeung, 2020), pandemi sonrası Çin müzik endüstirisi (Gu, Domer ve O'Connor, 2020), popüler müzik ve pandemi (Lehmen, 2020) konularında yapıldığı görülmüştür. Ayrıca sanat eğitiminde multimedia ve göz hareketleri (Ye vd., 2021), sanat terapisi (Potash vd., 2020), performans sanatları öğrencilerinin çevrimi öğrenmeye ilişkin algıları (Pratama & Surahman, 2020) ve pandemi döneminde radyo yayıncılığı (Munoz, 2021) alanlarında da çeşitli araştırmalar yapıldığı tespit edilmiştir.…”
Section: Dünyada Pandemi Sürecinde Sanat Ve Sanat Eğitimine İlişkin Araştırmalarunclassified
“…icra pratikleri (Cabedo-Mas, Arriaga-Sanz ve Moliner-Miravet, 2021; Chlu, 2020), çalgı eğitimcilerinin öğretme pratikleri (Bruin, 2021), yaşam doyumu, sosyal medya kullanımı ve müzik dinleme pratikleri (Krause vd., 2021), Amerika'da müziğin geleceği (Botstein, 2020), bütünsel iyilik, algılanan stres ve yenilikçi müzik terapi (Giardino vd.,, 2020; Gaddy vd., 2020), alkol, sigara ve ilaç bağımlılığı ve müzik terapi (Situmorang, 2020), İran müzik endüstrisi (Semati ve Behroozi, 2021), müzik ve pandemide kişilerarası ilişkiler (Philippe, Schiavio ve Biasutti, 2020), müzik tüketim araçları ve Spotify (Yeung, 2020), pandemi sonrası Çin müzik endüstirisi (Gu, Domer ve O'Connor, 2020), popüler müzik ve pandemi (Lehmen, 2020) konularında yapıldığı görülmüştür. Ayrıca sanat eğitiminde multimedia ve göz hareketleri (Ye vd., 2021), sanat terapisi (Potash vd., 2020), performans sanatları öğrencilerinin çevrimi öğrenmeye ilişkin algıları (Pratama & Surahman, 2020) ve pandemi döneminde radyo yayıncılığı (Munoz, 2021) alanlarında da çeşitli araştırmalar yapıldığı tespit edilmiştir.…”
Section: Dünyada Pandemi Sürecinde Sanat Ve Sanat Eğitimine İlişkin Araştırmalarunclassified
“…Although those highlighted statements have suggested the potentials of online teaching and learning approach in art classrooms, the migration from conventional to online teaching and learning approaches in art classrooms were reported to be far from its target (Sia & Abbas, 2020). For instance, a study by Pratama & Surahman (2020) has reported that the adoption of online learning in art classroom during pandemic are difficult and challenging, as it restrains student's creativity, artistic expression and understanding of art forms. Another biggest challenge in adopting online learning is to embody positive emotional engagement in learning among students (Dilmac, 2020).…”
Section: Online Teaching In Art Classroomsmentioning
confidence: 99%
“…Proses belajar mengajar di sekolah saat ini terkendala karena adanya pandemi COVID-19, tidak hanya sekolah bahkan sampai di tataran pendidikan tinggi seni (Pratama & Dewi, 2020;Pratama & Surahman, 2020). Masa darurat COVID-19 menuntut proses pembelajaran untuk dilakukan secara daring sesuai dengan Permendikbud No.…”
Section: Pendahuluanunclassified